Clinical Efficacy and Safety of Lacosamide as an Adjunctive Treatment in Adults With Refractory Epilepsy - Hou, Liyan; Peng, Bingjie; Zhang, Defu; Yang, Jingjing; Wang, Ying; Tong, Li; Li, Sheng; Wang, Qingshan; Zhao, Jie (Frontiers in Neurology, 2021)
Background: Lacosamide (LCM), a novel AED (antiepileptic drug), was used as an adjunctive treatment in patients with partial-onset seizures or without secondary generalization. However, no meta-analysis was performed to evaluate the efficacy of LCM as an adjunctive treatment in post-marketing clinical studies. Aims: To assess the safety and efficacy of LCM as an adjunctive treatment in adults with refractory epilepsy, a systematic review and meta-analysis of randomized controlled trials (RCTs) and real-world studies were performed. Methods: All studies were identified from electronic databases. Both RCTs and observational prospective studies were included. Primary outcomes included responder rate, adverse effects (AEs) and withdraw rate. The pooled rates (PR) with their corresponding 95% confidence intervals (CI) were calculated. Publication bias was assessed with Begg's or Egger's tests. Results: Total 16 studies (3,191 patients) including 5 RCTs and 11 real-word studies were enrolled. The pooled 50% responder rate and seizure-free rate were 48% (95% CI: 0.42, 0.54) and 9% (95% CI: 0.06, 0.11) in all studies, respectively. Subgroup analysis showed that the pooled 50% responder rate were 53% (95% CI: 0.44, 0.62) from observational studies and 38% (95% CI: 0.35, 0.42) from RCTs, respectively; the pooled seizure-free rate were 13% (95% CI: 0.09, 0.18) from observational studies and 4% (95% CI: 0.06, 0.11) from RCTs, respectively. Similar incidence of AEs were reported in real-world studies (0.57, 95% CI: 0.43, 0.72) and RCTs (0.59, 95% CI: 0.42–0.76). Finally, a total of 13% (95%CI: 0.09, 0.16) and 13% (95% CI: 0.08, 0.16) of all patients prescribed with LCM was withdrawn in RCTs and real-world studies, respectively, due to the occurrence of AEs. Furthermore, similar to the 50% responder rate, seizure-free rate, incidence of AEs and withdraw rate were reported at 6-month or at least 12-month of LCM adjunction. Publication bias was not detected in these studies. Conclusions: Our results revealed that LCM adjunctive therapy even with long-term treatment was efficacious and well tolerated in adults with refractory epilepsy.